SYSTEMIC GRANULOMATOSIS IN MEAGRE (ARGYROSOMUS REGIUS): A LINK WITH ATYPICAL MYCOBACTERIA - M. Polinas; C. Murgia; T. Cubeddu; M.A. Sanna; S. Dei Giudici; D. Schleicherová; A. Zanoli; G.P. Burrai; G. Barbera; M. Prearo; E. Antuofermo (Journal of Comparative Pathology, 2024)

First description of a mortality event in adult Pacific oysters in Italy associated with infection by a Tenacibaculum soleae strain - E A V Burioli; K Varello; S Trancart; E Bozzetta; A Gorla; M Prearo; M Houssin (Journal of Fish Diseases, 2018)
Summer mortality episodes in adult Pacific oysters have been described since the 1950s in various farming areas. Starting in 2012, a recrudescence of mortalities in commercial‐sized oysters was first observed in France and then in Italy, with seasonality extension and translation later in the year. Moribund individuals collected during an event in Italy in December 2014 showed yellowish lesions of the mantle and adductor muscle. Histological examination revealed filamentous bacteria associated with necrotic areas. Quantitative PCR s targeting Os HV ‐1 and Vibrio aestuarianus detected only high loads of the pathogenic bacteria in tissues of symptomatic individuals. A lower diversity of the hemolymph microbiota was also evidenced in moribund individuals, with a predominance of Vibrio and Arcobacter species. A strain of Flavobacteriaceae was isolated from all the symptomatic individuals. Sequence analysis of the 16S rRNA gene identified the strain as Tenacibaculum soleae . When strain pathogenicity was tested by injection in adult individuals, it induced mortality rates of up to 45%, even in the absence of V. aestuarianus . As mortality occurred only 11 days post‐infection, further investigation is needed to determine its effective virulence in natural conditions. This is the first description of a Tenacibaculum strain associated with bivalve mortalities.

Mycobacteriosis caused by Mycobacterium marinum in reared mullets: first evidence from Sardinia (Italy) - E Antuofermo; A Pais; M Polinas; T Cubeddu; M Righetti; M A Sanna; M Prearo (Journal of Fish Diseases, 2017)
Mycobacterium marinum is a slow‐growing non‐tuberculous mycobacterium, and it is considered the most common aetiologic agent of mycobacteriosis in wild and cultured fish. The diagnosis is principally made by histology when positive Ziehl–Neelsen stain granulomas are detected. The aim of this study was to investigate the occurrence of mycobacteriosis in extensively cultured Mugilidae of two lagoons (Cabras and San Teodoro) from Sardinia by the use of histology, microbiology, PCR and DNA sequencing. Nine of 106 mullets examined were affected by mycobacteriosis, and the spleen was the most affected organ. The histology detected higher rate (100%) of infection in spleen than the culture and PCR (75% and 62.5%, respectively). The sequencing of hsp65 gene identified M. marinum as the primary cause of mycobacteriosis in the mullets examined. Mullets affected by mycobacteriosis were mainly fished in the San Teodoro lagoon characterized by critical environmental conditions. Histology remains the most common method in detecting fish affected by mycobacteriosis, and PCR‐based methods are essential for species identification. Our finding are worthy of attention because mycobacteriosis caused by M. marinum in reared mullets was evidenced for the first time in Sardinia, suggesting that this disease may be underestimated also in other cultured fish species.

Molecular identification of iridoviruses infecting various sturgeon species in Europe - L Bigarré; M Lesne; A Lautraite; V Chesneau; A Leroux; M Jamin; P M Boitard; A Toffan; M Prearo; S Labrut; P Daniel (Journal of Fish Diseases, 2017)
Iridoviridae are known to cause disease in sturgeons in North America. Here, histological and molecular methods were used to screen for this family of virus in sturgeons from various European farms with low‐to‐high morbidity. Some histological samples revealed basophilic cells in the gill and labial epithelia, strongly suggesting the accumulation of iridovirus particles. Newly developed generic PCR tests targeting the major capsid protein ( MCP ) gene of sturgeon iridoviruses identified in North America, namely the white sturgeon iridovirus and the Namao virus ( NV ), produced positive signals in most samples from four sturgeon species: Russian ( Acipenser gueldenstaedtii ), Siberian ( A. baerii ), Adriatic ( A. naccarii ) and beluga ( Huso huso ). The sequences of the PCR products were generally highly similar one another, with nucleotide identities greater than 98%. They were also related to (74–88%), although distinct from, American sturgeon iridoviruses. These European viruses were thus considered variants of a single new virus, provisionally named Acipenser iridovirus‐European (Ac IV ‐E). Moreover, three samples infected with Ac IV ‐E showed genetic heterogeneity, with the co‐existence of two sequences differing by five nucleotides. One of our European samples carried a virus distinct from Ac IV ‐E, but closely related to NV identified in Canada (95%). This study demonstrates the presence of two distinct sturgeon iridoviruses in Europe: a new genotype Ac IV ‐E and an NV ‐related virus.

Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA): emerging contaminants of increasing concern in fish from Lake Varese, Italy - S. Squadrone; V. Ciccotelli; M. Prearo; L. Favaro; T. Scanzio; C. Foglini; M.C. Abete (Environmental Monitoring and Assessment, 2015)

Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, O ncorhynchus mykiss (Walbaum) - S Colussi; M Prearo; S A Bertuzzi; T Scanzio; S Peletto; L Favaro; P Modesto; M G Maniaci; G Ru; R Desiato; P L Acutis (Journal of Fish Diseases, 2015)
Major histocompatibility complex ( MHC ) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. L actococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, O ncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism ( SNP ) and one haplotype were associated with resistance ( P MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.

Mixed mycobacterial infection in an adult koi carp C yprinus carpio L - L Favaro; T Scanzio; K Varello; M Caffara; M Righetti; E Bozzetta; M Prearo (Journal of Fish Diseases, 2014)

Mycobacterium salmoniphilum infection in a farmed Russian sturgeon, Acipenser gueldenstaedtii (Brandt & Ratzeburg) - M Righetti; L Favaro; E Antuofermo; M Caffara; S Nuvoli; T Scanzio; M Prearo (Journal of Fish Diseases, 2014)

Granulomatous lesions in a wild mullet population from the eastern L igurian S ea ( I taly): mycobacteriosis vs . pseudotuberculosis - K Varello; M Prearo; L Serracca; D Meloni; I Rossini; M Righetti; M Pezzolato; M L Fioravanti; C Ercolini; E Bozzetta (Journal of Fish Diseases, 2014)
Mycobacterium spp. and P hotobacterium damselae subsp. piscicida are recognized as the most frequent causative agents of granulomatous lesions in fish. Although frequent episodes of mycobacterial infections have been reported in wild fish worldwide, only sporadic cases have been documented to date in Italy. To investigate for the presence of lesions referable to mycobacteriosis and to identify the mycobacterial species involved, a total of 159 wild mullets were fished from the eastern coast of the L igurian S ea, killed and necropsied. Liver and spleen samples were collected from all fish for histopathological and microbiological analyses. Molecular investigations for identification of P hotobacterium damselae subsp. piscicida were performed. Gross examination revealed granulomatous lesions in one animal; microscopically, 42.14% of fish displayed granulomas with various histological features, 19.50% resulted positive at Ziehl–Neelsen staining, and were confirmed as mycobacterial lesions by culture. The identified colonies were characterized as M. fortuitum, M. abscessus, M. flavescens, M. chelonae, M. septicum and M. nonchromogenicum . In all, 35% of animals resulted positive for P hotobacterium damselae subsp. piscicida . These data suggest widespread mycobacterial infection also by P hotobacterium damselae subsp. piscicida infections in wild fish. Moreover, the pathogenicity of some mycobacterial species, previously considered as saprophytic, was demonstrated.

Heavy metals in Mugil cephalus (Mugilidae) from the Ligurian Sea (North-West Mediterranean, Italy) - S. Squadrone; M. Prearo; S. Gavinelli; M. Pellegrino; R. Tarasco; A. Benedetto; M.C. Abete (Food Additives & Contaminants Part B-Surveillance, 2013)

Mycobacterium marinum infection in a hybrid striped bass farm in Italy - E Bozzetta; K Varello; I Giorgi; M L Fioravanti; M Pezzolato; R G Zanoni; M Prearo (Journal of Fish Diseases, 2010)

Occurrence of Mycobacterium spp. in ornamental fish in Italy - R G Zanoni; D Florio; M L Fioravanti; M Rossi; M Prearo (Journal of Fish Diseases, 2008)
The occurrence of Mycobacterium spp. in freshwater and marine ornamental fish was studied in Italy from June 2002 to May 2005. Two surveys were carried out, one of aquarium fish sent to the Laboratory for diagnosis, and the other of prevalence of infection by mycobacteria in ornamental fish imported into Italy. Bacterial isolation was carried out from the spleen, kidney and liver, and the isolates were subsequently identified by biochemical tests. In the first survey, 387 fish were examined and Mycobacterium spp. were isolated from 181 (46.8%) fish. In the second survey 127 batches of ornamental fish from different countries were examined. Mycobacterium spp. were isolated from 38 (29.9%) batches. The following species were found: M. fortuitum , M. peregrinum , M. chelonae , M. abscessus , M. marinum , M. gordonae , M. nonchromogenicum and M. interjectum . There was a high prevalence of infection independent of the presence of macroscopic lesions. Mycobacterium fortuitum and M. chelonae were more prevalent than M. marinum in the samples examined.

Mycobacterioses: Emerging Pathologies in Aquarium Fish - M. Prearo; R.G. Zanoni; B. Campo Dall'Orto; E. Pavoletti; D. Florio; V. Penati; C. Ghittino (Veterinary Research Communications, 2004)